APPLICABILITY OF M&A VALUATION MODELS IN THE PHARMACEUTICAL AND BIOTECHNOLOGY INDUSTRY - Lindéus, Gustav (Digital Repository of Theses, 2021)
The purpose of this research was to evaluate the applicability of M&A valuation models in the pharmaceutical and biotechnology industry. A quantitative study with secondary data, using two modelling approaches, DCF and relative valuation, was conducted. The choice of the two modelling approaches was a result of an extensive literature study of different approaches to valuation. The two modelling approaches were applied to six target companies, involved in M&A deals in the pharmaceutical and biotechnology industry during the last decade, which are widely known to not have been as successful as anticipated with respect to sales growth, market capitalization, profitability as well as other important metrics. These target companies were Monsanto, Actelion, Kite Pharma, Bioverativ, Cubist and Questcor Pharmaceuticals, which were acquired by Bayer, Johnson & Johnson, Gilead Sciences, Sanofi, Merck and Mallinckrodt respectively. Three research questions, related to differences between the models, sensitivity of assumptions and if the models contributed to reduction of important financial metrics such as sales growth as well as market capitalization, were answered in the thesis. Based on carefully chosen assumptions, the relative valuation generated more accurate and closer results to the realized enterprise values as well as share prices than the DCF approach. Within the relative valuation, the EV/Sales multiple was more accurate than the other studied multiples: EV/EBITDA and P/E. When adjusting various assumptions in the DCF model, some of the targets generated almost identical results as the realized values. Although being highly dependent on assumptions, both models tend to generate more undervalued results than overvalued ones, which may indicate that the valuation itself was not the major contributor to reduction of important financial metrics after realization of the M&A deals. Even though this study was unique that it combined the DCF and relative valuation modelling approaches and applied them to several companies at the same time, further research is needed to fully understand the applicability of M&A valuation in the pharmaceutical and biotechnology industry. A suggestion is to apply more targets to a similar study and perhaps also extend with other models.